2012
DOI: 10.1038/npp.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Modulates Reward System Activity During Subconscious Processing of Sexual Stimuli

Abstract: Dopaminergic medication influences conscious processing of rewarding stimuli, and is associated with impulsive-compulsive behaviors, such as hypersexuality. Previous studies have shown that subconscious subliminal presentation of sexual stimuli activates brain areas known to be part of the 'reward system'. In this study, it was hypothesized that dopamine modulates activation in key areas of the reward system, such as the nucleus accumbens, during subconscious processing of sexual stimuli. Young healthy males (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 61 publications
7
59
1
1
Order By: Relevance
“…In the case of MDMA, the additional release of NE may have had some small sexually enhancing effects, which were masked by concomitant 5-HT release, which is known to dampen sexual function (Pfaus, 2009). Consistent with our finding of increased sexual arousal after methylphenidate, the DA precursor levodopa enhanced the activation of the nucleus accumbens when subliminal sexual stimuli were shown, whereas the DA D 2 -receptor antagonist haloperidol decreased activations (Oei et al, 2012). Accordingly, the DA and NE transporter inhibitor and antidepressant bupropion, which has less side effects on sexual arousal and libido than serotonergic antidepressants, increased activation of brain regions related to sexual functioning (Abler et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…In the case of MDMA, the additional release of NE may have had some small sexually enhancing effects, which were masked by concomitant 5-HT release, which is known to dampen sexual function (Pfaus, 2009). Consistent with our finding of increased sexual arousal after methylphenidate, the DA precursor levodopa enhanced the activation of the nucleus accumbens when subliminal sexual stimuli were shown, whereas the DA D 2 -receptor antagonist haloperidol decreased activations (Oei et al, 2012). Accordingly, the DA and NE transporter inhibitor and antidepressant bupropion, which has less side effects on sexual arousal and libido than serotonergic antidepressants, increased activation of brain regions related to sexual functioning (Abler et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…In patients with Parkinson's Disease, increased sexual desire correlated with enhanced activation in the nucleus accumbens, cingulate cortex, and orbitofrontal cortex (Politis et al 2013). In healthy controls, dopamine agonism with l-dopa enhanced nucleus accumbens and anterior cingulate activation in response to subliminal sexual stimuli (Oei et al 2012), also consistent with a role for dopamine in processing of sexual stimuli, and -by implication -possibly compulsive sexual behaviour.…”
Section: Neurobiology Of Compulsive Sexual Behaviourmentioning
confidence: 77%
“…Apomorphine (a dopaminergic agonist) was found to be effective in erectile dysfunction [Mulhall et al 2001]. Another recent study showed that levodopa, another dopamine agonist, enhances activations in brain-reward systems associated with subliminal sexual stimuli [Oei et al 2012]. So, spontaneous ejaculations in this patient might be mediated through the dopaminergic system.…”
Section: Discussionmentioning
confidence: 80%